Nanocrystals for Improved Drug Delivery of Dexamethasone in Skin Investigated by EPR Spectroscopy - Silke B. Lohan; Siavash Saeidpour; Miriam Colombo; Sven Staufenbiel; Michael Unbehauen; Amanuel Wolde-Kidan; Roland R. Netz; Roland Bodmeier; Rainer Haag; Christian Teutloff; Robert Bittl; Martina C. Meinke (MDPI AG, 2020)
Nanocrystals represent an improvement over the traditional nanocarriers for dermal application, providing the advantages of 100% drug loading, a large surface area, increased adhesion, and the potential for hair follicle targeting. To investigate their advantage for drug delivery, compared to a base cream formulation, dexamethasone (Dx), a synthetic glucocorticoid frequently used for the treatment of inflammatory skin diseases, was covalently linked with the paramagnetic probe 3-(carboxy)-2,2,5,5-tetramethyl-1-pyrrolidinyloxy (PCA) to DxPCA. To investigate the penetration efficiency between these two vehicles, electron paramagnetic resonance (EPR) spectroscopy was used, which allows the quantification of a spin-labeled drug in different skin layers and the monitoring of the drug release. The penetration behavior in excised healthy and barrier-disrupted porcine skin was monitored by EPR, and subsequently analyzed using a numerical diffusion model. As a result, diffusion constants and free energy values in the different layers of the skin were identified for both formulations. Dx-nanocrystals showed a significantly increased drug amount that penetrated into viable epidermis and dermis of intact (factor 3) and barrier-disrupted skin (factor 2.1) compared to the base cream formulation. Furthermore, the observed fast delivery of the spin-labeled drug into the skin (80% DxPCA within 30 min) and a successive release from the aggregate unit into the viable tissue makes these nanocrystals very attractive for clinical applications.